AODTH-003 Vedolizumab clinical and post-marketing safety experience of opportunistic infections. (17th June 2017) - Ng, SC; Palo, W; Blake, A; Rana-Khan, Q; Bhayat, F
Abstract : Introduction: The risk of opportunistic infections (OIs) in inflammatory bowel disease increases with the use of biologics compared with placebo (odds ratio [OR]: 1.90). 1 Vedolizumab (VDZ), a humanised monoclonal antibody, targets α4 β7 integrin and selectively blocks gut-specific lymphocyte trafficking. Gut selectivity may be associated with a lower risk of infection compared with anti-tumour necrosis factor-alpha (TNFα) agents, which cause systemic immunosuppression. We assessed the frequency of OIs with VDZ in clinical trials and in the post-marketing (PM) setting. Method: Safety data from GEMINI 1 and 2 (VDZ vs placebo, in ulcerative colitis [UC] and Crohn's disease [CD], respectively), the ongoing GEMINI open-label extension (OLE) study (VDZ only, UC and CD; data cut-off: 19 May 2015) and the VDZ Global Safety Database (May 2014–30 September 2016) were assessed. OI events were identified from a list of Medical Dictionary for Regulatory Activities terms. Results: Seven of the 1434 VDZ-treated patients experienced OIs in GEMINI 1 and 2; no OIs were observed with placebo (n=297). OIs were Clostridium difficile colitis (n=5: n=1 considered serious, n=1 resulted in discontinuation), cytomegalovirus (CMV) colitis (n=1) and CMV infection (n=1). Of the 7 patients, 6 (86%) had prior exposure to anti-TNFα therapy. In the OLE (n=2243; total patient-years=5430), 51 patients reported OIs (n=18 serious; n=4 discontinuations). C. difficile colitis was most frequent (n=27). OIs rarely led to VDZ discontinuation (n=4 UC, 0.2%; none in CD) and there were no deaths due to OIs. In the context of ~72 140 patient-years of VDZ therapy in the PM setting, 127 OIs were reported in 124 patients (59 serious, 68 non-serious events); the most frequent was C. difficile infection (30 serious, 57 non-serious events). Two patients had fatal OIs: pneumocystis jirovecii pneumonia in a patient with immunosuppression due to long-term high-dose steroid use, and an unspecified OI in a patient with steroid-refractory graft versus host disease (off-label use). VDZ treatment was continued in most patients with OI events (66%). Conclusion: Clinical trial and PM data showed that OIs were infrequent with VDZ. The most common OI was C. difficile colitis/ C. difficile infection: most events were non-serious; most patients continued VDZ. Limitations with PM safety reporting (e.g. limited details in case reports, increased likelihood of reporting more severe events) must be considered when interpreting the PM data. W. Palo is now at Abbvie Inc., North Chicago, IL, USA Reference: . Bonovas S, et al. Clin Gastroenterol Hepatol2016;14:1385. Disclosure of Interest: S. Ng Conflict with: Janssen, Abbvie, Takeda, Conflict with: Lecture fees: Takeda, Menarini, W. Palo Conflict with: Takeda Development Centre Americas, Inc.; Abbvie Inc., A. Blake Conflict with: Takeda Development Centre Europe Ltd, Q. Rana-Khan Conflict with: Takeda Pharmaceutical International AG Singapore, F. Bhayat Conflict with: Takeda Development Centre Europe Ltd